Characteristics of solar wind control on Jovian UV auroral activity deciphered by long‐term Hisaki EXCEED observations: Evidence of preconditioning of the magnetosphere?. Issue 13 (8th July 2016) - Kita, Hajime; Kimura, Tomoki; Tao, Chihiro; Tsuchiya, Fuminori; Misawa, Hiroaki; Sakanoi, Takeshi; Kasaba, Yasumasa; Murakami, Go; Yoshioka, Kazuo; Yamazaki, Atsushi; Yoshikawa, Ichiro; Fujimoto, Masaki
Abstract: While the Jovian magnetosphere is known to have the internal source for its activity, it is reported to be under the influence of the solar wind as well. Here we report the statistical relationship between the total power of the Jovian ultraviolet aurora and the solar wind properties found from long‐term monitoring by the spectrometer EXCEED (Extreme Ultraviolet Spectroscope for Exospheric Dynamics) on board the Hisaki satellite. Superposed epoch analysis indicates that auroral total power increases when an enhanced solar wind dynamic pressure hits the magnetosphere. Furthermore, the auroral total power shows a positive correlation with the duration of a quiescent interval of the solar wind that is present before a rise in the dynamic pressure, more than with the amplitude of dynamic pressure increase. These statistical characteristics define the next step to unveil the physical mechanism of the solar wind control on the Jovian magnetospheric dynamics. Key Points: Superposed epoch analysis indicates the Jovian ultraviolet auroral power to increase with a rise in the solar wind dynamic pressure Auroral power enhancements clearly correlate with the durations of the preluding quiescent solar wind Auroral power enhancements do not clearly correlate with the amplitudes of the solar wind dynamic pressure enhancements